Palladium-Mediated Total Synthesis of Bioactive Natural Products - Majumdar, K. C.; Sinha, Biswajit (Synthesis, 2013)
The search for efficient synthetic procedures for natural products, drugs, and materials with economical and ecological advantages is an important area of current interst in synthetic organic chemistry. We have made an attempt to summarize the progress made in this area since 2005. This article describes the syntheses of several natural products and drugs that employ multiple palladium-catalyzed processes in either a sequential or a domino fashion.1Introduction2 Palladium-Mediated Synthesis of Alkaloids2.1 Indole Alkaloids2.2 Carbazole Alkaloids2.3 Quinoline and Isoquinoline Alkaloids2.4 Pyrrole and Pyridine Alkaloids2.5 Pyrrolizidine and Indolizidine Alkaloids2.6 Imidazole and Guanidine Alkaloids2.7 Other Alkaloids3 Palladium-Mediated Synthesis of Natural Products Containing a Sugar Moiety4 Palladium-Mediated Synthesis of Marine Natural Products5 Palladium-Mediated Synthesis of Amino Acids and Peptides6 Palladium-Mediated Synthesis of Terpenoids7 Miscellaneous Natural Products8 Conclusion
Keywords: palladium catalysis; natural product synthesis; biological activity; terpenoids; alkaloids; marine natural products; asymmetric allylic alkylation; C–H activation